Identifying diurnal cortisol profiles among young adults: Physiological signatures of mental health trajectories. (June 2021) - Hoyt, Lindsay Till; Zeiders, Katharine H.; Chaku, Natasha; Niu, Li; Cook, Stephanie H.
Abstract: Previous research has used cortisol, the major hormonal byproduct of the hypothalamic pituitary adrenal (HPA) axis system, to explore how environmental stressors influence daily physiological functioning. Most of the research focused on diurnal cortisol has examined specific cortisol markers, with little consideration of how different components of the diurnal pattern may co-occur. Morning level, cortisol awakening response (CAR), bedtime level, as well as the diurnal slope and total cortisol exposure throughout the day (area under the curve; AUC), are five common parameters of diurnal HPA axis functioning that have been individually linked to physical and mental health outcomes, with mixed results. The current study introduces a novel approach to capture heterogeneity in HPA axis activity by using latent profile analysis to generate empirically-derived, theoretically supported diurnal cortisol profiles based on all five indicators. We analyzed salivary cortisol data from 278 young adults during a time of heightened sociopolitical stress – the 2016 U.S. presidential election – and examined whether profiles differentially predicted mental health trajectories across six months. Findings suggest that a specific combination of cortisol parameters (i.e., flat slope, high AUC, and high CAR) may predict worse mental health risk over time. Overall, this work suggests that diurnal cortisol profiles likely reflect distinct physiological underpinnings with unique health consequences that may not be observed by studying individual cortisol parameters. Highlights: We identified four configurations of diurnal cortisol activity among young adults. Profiles capture heterogeneity in hypothalamic pituitary adrenal axis activity. Distinct cortisol profiles are associated with unique mental health trajectories.